MITK Phenotyping: an open-source toolchain for image-based personalized medicine with radiomics - Götz, Michael; Nolden, Marco; Maier-Hein, Klaus H. (Radiotherapy and oncology, 2019)
Radiomics - The extraction of quantitative features from radiologic images - shows increasing potential in contributing to modern personalized medicine approaches. MITK Phenotyping is an openly distributed radiomics framework implementing an exhaustive set of features, adhering to most recent international standards, and supporting a variety of different user interfaces and programming languages.
Available online 31 December 2018
Gesehen am 24.09.2019